Syllabic rhotics or vowel-rhotic sequences? an acoustic study of Czech, Slovak and Croatian syllabic rhotics - Sylwester Jaworski, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present article reports the results of an acoustic analysis of Czech, Slovak and Croatian words containing a syllabic rhotic, with a view to determining whether rhotics of this type should be regarded as syllabic consonants or rather as vowel-rhotic sequences, due to being preceded by an intrusive vocalic element. The primary objective of the study was to describe the temporal and spectral properties of intrusive vocalic elements that precede and sometimes follow the rhotic segment in order to define the extent to which they vary in the three languages. To achieve the aim, an acoustic analysis of samples of read speech was performed. The recordings were obtained from native speakers of Croatian, Czech and Slovak who read a list of words embedded in a carrier phrase. The analysis of the temporal data was meant to reveal whether the syllabic rhotics of the three languages are developing towards becoming vowel-rhotic sequences, which has recently occurred in Slovene. Syllabic rhotics, usually realised as taps, are normally flanked by vocalic segments that not only have a distinct formant structure, but also appear to be sufficiently long to determine their quality. The analysis points to the conclusion that intrusive vocalic elements are schwa-like segments in the sense that the values of their formants (F1 and F2) tend to be similar to those of the schwa vowel. Also, the findings reveal that the average duration of the intrusive segments is considerably longer in Croatian than in Czech and Slovak. Thus, the results indicate that a sound change might be taking place in Croatian.